The Moral Austerity of Environmental Decision Making : Sustainability, Democracy, and Normative Argument in Policy and Law - Bowersox, Joe, 1963-; Gillroy, John Martin, 1954- (Book collections on Project MUSE., 2002)
A roundtable discussion on the missing ethical dimension in environmental policy.